2017
DOI: 10.5812/pedinfect.57263
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aminoglycoside Resistance Genes Among Acinetobacter Baumannii Strains Isolated From Burn Patients in Tehran, Iran

Abstract: Background: Acinetobacter baumannii is an important cause of nosocomial infections, particularly in burn patients. Hospital Infections caused by these bacteria are difficult to treat. Objectives: The present study aimed at determining the frequency of genes encoding aminoglycoside-modifying enzymes in A. baumannii strains isolated from burn patients in Shahid Motahari hospital. Methods: This study was performed on 100 A. baumannii strains collected from Shahid Motahari hospital in Tehran during 2013 and 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…As expected, the most effective antibiotic with appreciable activity against the studied isolates was colistin. In agreement with our data, the results of previous studies in Iran ( 29 , 34 , 35 ) have shown that colistin-based therapy for treatment of diseases caused by MDR-AB had an appropriate clinical manifestation and decreased mortality.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the most effective antibiotic with appreciable activity against the studied isolates was colistin. In agreement with our data, the results of previous studies in Iran ( 29 , 34 , 35 ) have shown that colistin-based therapy for treatment of diseases caused by MDR-AB had an appropriate clinical manifestation and decreased mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Then, DNA templates were prepared using the DNA extraction kit (Genet Bio Company, Korea, Cat. No, K-3000) as previously described 18…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, prolonged hospitalization in the intensive care unit, severe illnesses, immunodeficiency conditions, burn injuries, long-term use of antimicrobial agents, and catheter use are some of the most important risk factors for Acinetobacter infection [ 5 ]. A. baumannii is an important opportunistic pathogen responsible for a variety of nosocomial infections; including ventilator-associated pneumonia, bacteremia, surgical site infections, secondary infections of burn patients, secondary meningitis, and urinary tract infections in the Middle East region [ 6 , 7 ] and other parts of the world [ 8 , 9 ]. Hydrolysis of the β-lactam ring structure by ESBL causes an abnormal antibiotic function.…”
Section: Introductionmentioning
confidence: 99%